2022
DOI: 10.1136/bmjopen-2021-060378
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide population-based study of poisoning-induced out-of-hospital cardiac arrest in South Korea

Abstract: ObjectiveTo evaluate the characteristics of poisoning-induced out-of-hospital cardiac arrest (pOHCA) and the factors influencing survival to discharge and good neurological outcomes using a nationwide, population-based database.DesignNationwide, retrospective, population-based cohort study.Setting and participantsThis study included adult patients who had experienced pOHCA and those who had not (non-pOHCA patients) in South Korea from January 2008 to December 2018.Outcome measuresThe primary outcome was surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, the sale and distribution of these highly toxic pesticides were completely prohibited by 2012 [15,16]. This regulation not only restricted the general public's access to pesticides but also significantly reduced the number of poisonings caused by pesticides [3]. Studies have reported a decline in poisoningrelated fatalities in other nations caused by similar restrictions on toxic substances [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the sale and distribution of these highly toxic pesticides were completely prohibited by 2012 [15,16]. This regulation not only restricted the general public's access to pesticides but also significantly reduced the number of poisonings caused by pesticides [3]. Studies have reported a decline in poisoningrelated fatalities in other nations caused by similar restrictions on toxic substances [17].…”
Section: Discussionmentioning
confidence: 99%
“…Land et al [19] (2021) focused on adult opioid poisonings in the United States and revealed a decline in overall opioid poisonings but an alarming increase in illicit opioid poisonings since 2010, indicating shifting dynamics in substance abuse [19]. Patients in South Korea differ because of the low frequency of deaths due to opioids [3], as confirmed by the recent trends. Additionally, Hernández-Calle et al [20] (2022) in Spain revealed increasing trends in both accidental and intentional drug poisonings among older adults [20], congruent with this observation of the heightened vulnerability of older adults in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations